1072 Review of Current Opinion and Availability of Cerebral Function Monitoring and Therapeutic Hypothermia in UK Neonatal Units. (October 2012) - Zipitis, CS; Sylvan, A; Harte, T; Hurst, S; Glover, K
Abstract : Background and Aims: Therapeutic hypothermia has been established as an effective treatment modality for term neonates that have suffered an acute perinatal hypoxic ischaemic event. This is a time-critical procedure which increases pressure to commence active cooling as soon as possible after the injury. This study aims to define the current levels of ownership of CFM and cooling equipment and capture some staff perceptions around cooling matters in neonatal units in the UK. Methods: Telephone survey conducted over March-November 2011 with the 205 active neonatal units listed on the British Association of Perinatal Medicine website. Results: 100% response-rate (205/205). 141 (68.8%) responders were Lead Nurse/Sisters, 59 (28.8%) were Nurses and 5 (2.4%) were Doctors. Overall, CFM was available at 106/205 (51.7%) units and 89/205 (43.4%) had cooling equipment. Equipment ownership was high in NICUs and progressively decreased in LNUs and SCBUs. The majority of responders were positive to the idea of therapeutic hypothermia as a standard of care whilst some asked for further research; only a small minority were negative. 91.6% were keen to consider a scheme where therapeutic hypothermia was initiated at the referring centre and continued in a dedicated cooling centre. Conclusions: Therapeutic hypothermia is widely recognised as effective. Availability of cooling equipment and CFM has increased in all levels of units in the UK. The time-constraints in initiating therapeutic hypothermia might mean that a scheme of initiating therapeutic hypothermia locally, continuing this during transport and completing it in a designated cooling centre is the way forward.